Donor Functionalization Tuning the N‐Type Performance of Donor–Acceptor Copolymers for Aqueous‐Based Electrochemical Devices. (4th May 2022) - Cong, Shengyu; Chen, Junxin; Wang, Lewen; Lan, Liuyuan; Wang, Yazhou; Dai, Haojie; Liao, Hailiang; Zhou, Yecheng; Yu, Yaping; Duan, Jiayao; Li, Zhengke; McCulloch, Iain; et al.
Abstract: In this work, three n‐type donor–acceptor copolymers consisting of glycolated naphthalene tetracarboxylicdiimide (gNDI) coupled with variable donating companion moieties are reported. Using 2, 2′‐bis(3, 4‐ethylenedioxy)bithiophene, 2, ​2′‐​bithiophene, 3, 3′‐difluoro‐2, 2′‐bithiophene (FBT), the donating strength of the donor units is systematically functionalized. These copolymers are used as a platform for aqueous‐based electrochemical devices, including energy‐storage devices, electrochromic devices (ECDs), and organic electrochemical transistors (OECTs). It is found that the electrochemical redox stability and electron mobility of copolymers are significantly improved via weakening the electron‐donating strength of donor units. gNDI coupling with FBT (gNDI‐FBT) exhibits a charge‐storage capacity exceeding 190 Fg −1, which is the highest value reported to date for NDI‐based polymer electrodes in aqueous media. For ECDs, gNDI‐FBT remains 100% of initial electrochromism contrast (∆ % T  = 20%) up to 1200 s. In addition, gNDI‐FBT outperforms its two analogs in OECTs, including lower threshold voltage (0.19 V), faster response time (45.5 ms), and higher volumetric capacitance (197 F cm −3 ). Moreover, gNDI‐FBT with fluorine atoms leads to the bipolarons delocalization along the polymer backbone and favorable molecular packing for ion–electron transport. Through such weak donor functionalization strategy, this work provides ways for n‐type copolymers tuning to access desirable performance metrics in optical, electrochemical, and bioelectronic applications. Abstract : Three glycolated n‐type naphthalene tetracarboxylicdiimide‐based copolymers coupled with variable electron‐donating companion moieties are used for aqueous‐based electrochemical devices. Weakening the electron‐donating strength of donor units leads to improved electrochemical redox stability, electron mobility, delocalized bipolarons distribution, and favorable molecular packing for ion–electron transport. Through weak donor strategy, n‐type copolymers can access desirable performance metrics in optical, electrochemical, and bioelectronic applications.